Diagnostic and prognostic significance of serum miR-145-5p expression in glioblastoma - Zhang, Yao (Int J Clin Exp Pathol, 2019)
MicroRNA-145-5p downregulation has been shown to play important roles in the oncogenesis and progression of many cancer types including glioblastoma (GBM). However, the potential role of serum miR-145-5p in the diagnosis and prognosis of glioblastoma (GBM) remains poorly known. This study was designed to explore the clinical significance of serum miR-145-5p in patients with GBM. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was carried out to measure the serum levels of miR-145-5p in 117 GBM patients, 52 grade I/II glioma patients and 50 healthy volunteers. The associations between serum miR-145-5p level and the clinical variables as well as prognosis were analyzed. The bioinformatic analysis of the downstream targets of miR-145-5p was also performed. Compared to grade I/II glioma patients and healthy controls, serum miR-145-5p levels were significantly decreased in GBM patients. In addition, the receiver operating characteristic (ROC) analysis demonstrated that serum miR-145-5p might be a reliable diagnostic marker of GBM with an AUC of 0.895, combing with 84.6% sensitivity and 78.0% specificity. Low serum miR-145-5p level had significant correlation with aggressive clinicopathological parameters. Moreover, the Kaplan-Meier curve revealed that patients in the high serum miR-145-5p group survived significantly longer than those in the low serum miR-145-5p group. Multivariate analysis confirmed that serum miR-145-5p expression was an independent prognostic indicator for overall survival. The bioinformatic analysis revealed that many downstream genes and pathways that miR-145-5p regulated were closely associated with the initiation and development of cancer. Taken together, decreased serum miR-145-5p is a promising diagnostic and prognostic biomarker for GBM.